Phase equilibria constraints on pre-eruptive magma storage conditions for the 1956 eruption of Bezymianny Volcano, Kamchatka, Russia - Shcherbakov Vasily D.; Neill Owen K.; Izbekov Pavel E.; Plechov Pavel Yu. (My University, 2013)
Phase equilibria experiments were performed on andesites from the catastrophic 1956 eruption of Bezymianny Volcano, Kamchatka, Russia, to determine pre-eruptive magma storage conditions. Fifteen experiments were conducted under water-saturated conditions, with oxygen fugacity equal to the Ni–NiO oxygen buffer, at temperatures between 775 and 1100 °C and pressures between 50 and 200 MPa. Simultaneous amphibole and plagioclase crystallization is reproduced at ≤850 °C and ≥200 MPa. The simultaneous crystallization temperature range of the plagioclase–clinopyroxene–orthopyroxene–Fe–Ti oxide assemblage increases with decreasing pressure, from 840 to 940 °C at 150 MPa to 940–1020 °C at 50 MPa. Melt inclusion compositions in plagioclase phenocrysts and matrix glass match experimental melt compositions reproduced at 50–100 MPa and ≤ 50 MPa, respectively. Presence of the silica phase in groundmass and mature amphibole breakdown rims suggests that magma has been stored at ca. 3 km depth prior to the final ascent for at least 40 days. Syn-eruptive ascent led to decompression-driven crystallization, which caused a temperature increase from 850–900 °C to 950–1000 °C.
Keywords: 38.37.25 Вулканология; Безымянный; Kamchatka